Characterizing Fatty Acid Profiles and Evaluating Antibacterial Activity of Edible Yellow Puffer Fish, Xenopterus naritus - SAMSUR, MOHAMAD; NUR EQMAL DINIE, NOR AZMI; ZAINI, ASSIM; AHMAD SYAFIQ, AHMAD NASIR; JULIAN, RANSANGAN; RABUYAH, NI (UNIMAS Publisher, 2024)
Puffer fish oil extracted from Xenopterus naritus represents a beneficial source of bioactive compounds with health-promoting properties. Despite the known benefits of puffer fish oil, there is a lack of detailed information on its fatty acid composition. This study aimed to fill this gap by investigating the fatty acid profiles of puffer fish oil extracted from the liver and muscle tissues. The oil was extracted using the solvent Bligh & Dyer method, and the samples were derivatized into fatty acid methyl esters (FAME) before being analyzed via Shimadzu QP2010 Plus gas chromatography-mass spectrometry (GC-MS). This analysis highlighted the prevalence of omega-3 fatty acids, particularly Docosahexaenoic acid (DHA) (8.28 ± 0.08% in liver, 6.15 ± 0.33% in muscle oil) and Eicosapentaenoic acid (EPA) (3.29 ± 0.12% in liver and 2.16 ± 0.06% in muscle oil), along with the abundance of omega-6 and omega-9 fatty acids, including arachidonic and oleic acid. Additionally, the antimicrobial properties of these fish oils were assessed against Gram-negative and Gram-positive bacteria using the Minimum Inhibitory Concentration (MIC) method, revealing promising inhibitory effects, with liver oil demonstrating greater efficacy. These findings suggest that puffer fish oil is rich in beneficial fatty acids and possesses antimicrobial properties that could find applications in food preservation, medicine, and agriculture, thereby offering a fresh perspective on the functional and nutritional value of Xenopterus naritus.